2013
DOI: 10.1128/aac.00750-13
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin and Tobramycin in Combination Downregulate Nitrate Reductase Genes narG and narH , Resulting in Increased Activity against Pseudomonas aeruginosa under Anaerobic Conditions

Abstract: e The activity of aminoglycosides, which are used to treat Pseudomonas aeruginosa respiratory infection in cystic fibrosis (CF) patients, is reduced under the anaerobic conditions that reflect the CF lung in vivo. In contrast, a 4:1 (wt/wt) combination of fosfomycin and tobramycin (F:T), which is under investigation for use in the treatment of CF lung infection, has increased activity against P. aeruginosa under anaerobic conditions. The aim of this study was to elucidate the mechanisms underlying the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Since the course of some infections, such as biofilm-mediated ones, develop in microaerobic environments or in completely anaerobic conditions, such as cystic fibrosis chronic infections (26,27), the development of resistant mutants was tested also in anaerobiosis. It is known that aminoglycosides are less active in anaerobiosis because their penetration into bacterial cells depends on an oxygen-dependent reaction (28). This fact reinforces the need to administer tobramycin in combination with other compounds.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Since the course of some infections, such as biofilm-mediated ones, develop in microaerobic environments or in completely anaerobic conditions, such as cystic fibrosis chronic infections (26,27), the development of resistant mutants was tested also in anaerobiosis. It is known that aminoglycosides are less active in anaerobiosis because their penetration into bacterial cells depends on an oxygen-dependent reaction (28). This fact reinforces the need to administer tobramycin in combination with other compounds.…”
Section: Discussionmentioning
confidence: 79%
“…Fosfomycin has demonstrated that it can enhance the active transport of tobramy- cin into the cell (10); furthermore, its activity does not decrease in anaerobiosis, and some studies have reported high activity under these conditions (16). It has also been reported that fosfomycintobramycin association is advantageous in anaerobiosis, as it downregulates the expression of nitrate reductase genes that are essential for the growth of P. aeruginosa (28). As has been previously described, fosfomycin-tobramycin combination is capable of eradicating P. aeruginosa biofilm growth on cystic fibrosis-derived airway cells (6) and of improving the therapeutic effect in a biofilm-infected animal model (29).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FTI has in vitro activity against other pathogens including H. influenzae, S. aureus, and MRSA and importantly, it has been shown to be active against P. aeruginosa in anaerobic conditions [245].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is probable that other coexisting mechanisms conferring resistance, including efflux pumps and modified antibiotic targets, and transferred together with ESBL genes in the same or conjugated plasmids contribute to these phenotypes. Enhanced antibiotic uptake (168) or downregulation of vital genes for bacterial growth (169), as shown for tobramycin in the presence of mucin and under anaerobic conditions in patients with cystic fibrosis, may also contribute to the synergistic activity. Future studies should compare the outcomes for patients infected by bacteria which were susceptible to antibiotic combinations in vitro to those for patients infected by bacteria that remained resistant.…”
Section: Newer Studiesmentioning
confidence: 99%